Alternative approaches for enhancing plasmonic sensor performance - Soehartono, Alana Mauluidy (Nanyang Technological University, 2020)
Strong light localization near metal nanostructures occurs by collective oscillations of plasmons in the form of electric and magnetic resonances. The high susceptibility of such localized surface plasmons (LSP) to refractive index changes has made it an excellent platform for rapid and label-free sensing, particularly in the development of low-cost sensing platforms in the visible spectrum. However, the linear relationship between sensitivity and resonance wavelength indicates that sensitivity decreases for shorter wavelengths. In this thesis, alternative plasmon resonance mechanisms are explored to address the challenges of plasmonic sensing in the visible frequency range. The numerical and experimental investigation of the magnetic-type LSP resonance is contrasted with the electric-type used in conventional LSP-based sensing. The role of geometry, especially height, on the resonance mechanisms is also studied, in which it is found that higher aspect ratio structures, realized by a cost-effective electrodeposition process, support waveguide-like modes which outperform typical planar resonances by up to 3X in the sensitivity and 10X in the figure of merit for the bulk and surface aspects. Furthermore, the practical implications of the work are discussed.